CAN THE INTERNET HELP RELIEVE DEPRESSION? - Chen, Yizhe (PEOPLE: International Journal of Social Sciences, 2019)
Depression is a very serious problem in our modern society. It can influence people negatively in many ways. Although many scientists are trying to find efficient ways to deal with depression, there are still no final conclusions. Using data from the China Health and Retirement Longitudinal Study (CHARLS), this study shows that in China, internet use among older people (aged 45 and above) helps relieve their depression symptoms. Combining this finding with steadily growing cellphone use, this suggests that developing specially APPs for older people to use smart phones can help combat depression in China. Other ways to reach the rural population via the internet can also be powerful tools to help with depression.